2020
DOI: 10.1074/jbc.rev119.009710
|View full text |Cite
|
Sign up to set email alerts
|

Extra-telomeric impact of telomeres: Emerging molecular connections in pluripotency or stemness

Abstract: Telomeres comprise specialized nucleic acid–protein complexes that help protect chromosome ends from DNA damage. Moreover, telomeres associate with sub-telomeric regions through looping. This results in altered expression of sub-telomeric genes. Recent observations further reveal telomere length dependent gene regulation and epigenetic modifications at sites spread across the genome and distant from telomeres. This regulation is mediated through the telomere-binding protein telomeric repeat–binding factor 2 (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 125 publications
(139 reference statements)
1
15
0
Order By: Relevance
“…Although further work will be required to test this, based on our findings here, it is possible that establishment of a telomeretelomerase crosstalk through TRF2 (telomeric along with non-telomeric binding at the hTERT promoter) is key to how telomeres are managed in cancer cells. In addition, relatively enhanced levels of telomerase and long telomeres are crucial for maintenance/survival of pluripotent stem cells (Aguado et al, 2017;Vinayagamurthy et al, 2020;Zou et al, 2017) It is possible, therefore, that TRF2-mediated hTERT regulation, linked to telomeres, is of significance in pluripotency. Kim et al (2016) showed looping of the 5p chromosome telomere to a region $1.2 Mb away and 100 kb downstream of hTERT.…”
Section: Discussionmentioning
confidence: 99%
“…Although further work will be required to test this, based on our findings here, it is possible that establishment of a telomeretelomerase crosstalk through TRF2 (telomeric along with non-telomeric binding at the hTERT promoter) is key to how telomeres are managed in cancer cells. In addition, relatively enhanced levels of telomerase and long telomeres are crucial for maintenance/survival of pluripotent stem cells (Aguado et al, 2017;Vinayagamurthy et al, 2020;Zou et al, 2017) It is possible, therefore, that TRF2-mediated hTERT regulation, linked to telomeres, is of significance in pluripotency. Kim et al (2016) showed looping of the 5p chromosome telomere to a region $1.2 Mb away and 100 kb downstream of hTERT.…”
Section: Discussionmentioning
confidence: 99%
“…When gene silencing occurs over long-distances of DNA via long telomeres looping back in the chromatin, the phenomenon is referred to as TPE-over long distances or TPE-OLD. The expression of hTERT is thought to be regulated by a TPE-OLD [ 155 , 156 ]. Both TTP1 and POT1 are involved in regulating telomerase by promoting processivity.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is known as telomere positioning effect (TPE). Telomere looping does also occur over long distances so that TPEs can influence the expression of distant genes (TP-OLD) [6,7]. Short telomeres are no longer able to maintain their complex three-dimensional structure, which abolishes TPE and TPE-OLD.…”
Section: Introductionmentioning
confidence: 99%